Acute vowels a and e in Kuršaitis’ dictionaries - Strockis, Mindaugas (Baltistica, 2019)
Most modern manuals of Lithuanian accentuation traditionally adhere to the doctrine that the vowels a and e cannot have the acute tone except in diphthongs. Yet software-assisted analysis of the digitised texts of the German-Lithuanian (1870–1874) and Lithuanian-German (1883) dictionaries of Fridrikis Kuršaitis (in German known as Friedrich Kurschat) reveals that the existence of these monophthongs with the acute tone is real and well attested, at least in the variety of Lithuanian once spoken in Lithuania Minor, as described by Kuršaitis. A considerable proportion of the words with these acute-tone vowels consists of loanwords of various origins, among them geographical names: páslas (‘envoy’), áptas (‘abbot’), telegráfas (‘telegraph’), gimnázija (‘gymnasium’, a type of secondary school), Galátija (‘Galatia’), Ázija (‘Asia’) etc.